Lactobacilli species diversity in gut microbiota of renal failure patients - Gholamreza Hanifi; Hossein Samadi Kafil; Hamid Tayebi Khosroshahi; Reza Shapouri; Mohammad Asgharzadeh (Journal of King Saud University: Science, 2020)
Lactobacillus species and other acid producing bacteria could inhibit aerobic bacteria, normalize the intestinal microbiota and decrease the uremic toxins in patients with chronic kidney disease. Therefore, the aim of this study is assessment of abundance of lactobacillus spp. in fecal flora of End-stage kidney disease (ESKD) and kidney transplanted patients. DNA of 20 fecal samples of ESKD and kidney-transplanted as patients group and 20 fecal samples of non-ESKD and -kidney-transplanted as control group, which were admitted to hospitals, were extracted. Amplified DNA by 16srRNA illumina V3 and V4 primers were sequenced by MiSeq system. Total 651 strains, 37 (5.68%) strains were identified as order Lactobacillales. The strains were classified into six family, nine genus and 37 species. The most abundance genus in both groups are Streptococcus spp. and Lactobacillus spp. and the lowest abundance genus in both groups are Pediococcus and Leuconostoc. Comparing the abundance mean of the strains revealed that there is no significant association between control group and disease group, but the abundance mean of the strains in control group increase in compared to disease group. More diversity was exhibited in lactobacillus spp. in patients with chronic kidney disease compared to control group. Some of the species of Lactobacillaceae family such as L. acidophilus was not found in both patients and control groups. In addition, more of the species of Lactobacillaceae were decreased in patients group, whereas certain species were increased in patients group compared to control group.